Twin growth discordance in association with maternal exposure to fine particulate matter and its chemical constituents during late pregnancy - Ping Qiao (Environment International, 2019)
Background: Twin growth discordance is one of the leading causes of perinatal mortality in twin pregnancies. Whether prenatal exposure to fine particle (PM2.5) air pollution is associated with twin growth discordance have not been studied yet. Objective: To evaluate the associations of prenatal exposure to PM2.5 and its chemical constituents with twin growth discordance. Methods: This study included 1917 twin pairs and their mothers drawn from a previous twin birth cohort at the Shanghai First Maternity and Infant hospital in Shanghai, China. Exposure to PM2.5 total mass and 6 key chemical constituents during the whole pregnancy and each trimester of pregnancy was represented by satellite-based models. Results: Maternal exposures to PM2.5 total mass and chemical constituents of sulfate (SO42−) and ammonium (NH4+) during the third trimester were significantly associated with increased within-pair birth weight difference and intertwin birth weight discordance. The within-pair birth weight difference increased by 30.6 g (β = 30.6, 95% CI, 4.4–56.9), 19.2 g (β = 19.2, 95% CI, 0.2–38.1) and 33.2 g (β = 33.2, 95% CI, 7.9–58.6) for an IQR increase in PM2.5 total mass, SO42− and NH4+ exposure, respectively. While the intertwin birth weight discordance increased by 1.3% (β = 1.3, 95% CI, 0.3–2.2), 0.9% (β = 0.9, 95% CI, 0.2–1.6) and 1.4% (β = 1.4, 95% CI, 0.4–2.3) for the same exposure metrics. Moreover, higher SO42− and NH4+ exposure was also associated with increased risk of twin growth discordance in linear dose-response manners. Compared to the lowest quartile of SO42− (OR = 2.51, 95% CI, 1.08–5.82) and NH4+ (OR = 2.97, 95% CI, 1.16–7.58) exposure, the odds of twin growth discordance were doubled in highest quartile of exposure. Conclusion: Our results suggest that fine particle air pollution may be a risk factor for twin growth discordance. Late pregnancy seems to be a critical window for the effects of PM2.5 exposure on fetal growth in twins. Keywords: Ambient air pollution, PM2.5, Chemical constituents, Within-pair birth weight difference, Twin growth discordance